Energy and exergy and economic (3E) analysis of a two-stage organic Rankine cycle for single flash geothermal power plant exhaust exergy recovery. (December 2021) - Fan, Guangli; Gao, Yingjie; Ayed, Hamdi; Marzouki, Riadh; Aryanfar, Yashar; Jarad, Fahd; Guo, Peixi
Abstract: A two-stage ORC (Organic Rankine Cycle) is being proposed for the recovery and utilization of low-grade heat from single flash geothermal power plant exhaust flue fluids. The working fluids for two-stage the recovery system are R227ea and R116. The impact of essential design parameters such as inlet temperature of the cycle, ambient temperature, geothermal turbine inlet pressure, geothermal condensation temperature on system performance are investigated using thermodynamic mathematical models regarding energy and exergy efficiencies as the objective function. The addition of the recovery section to the base cycle improves the thermal efficiency from 0.2023 to 0.2178, a 7.66% improvement in this critical metric. Furthermore, the exergy efficiency rises from 0.55044 to 0.5803, representing a 15.04% boost in exergy efficiency. Furthermore, the system's overall output rises from 7690 kW to 9898 kW, representing a substantial gain of 28.71%. The suggested recovery system's cycle has a lower LEC than a single flash geothermal cycle from an economic standpoint. LEC Reduced from 0.125 per kilowatt to 0.108 per kw, a cost savings. As a result, including a recovery section in the basic single flash geothermal cycle will significantly improve system performance. Graphical abstract: Image 1